Efektivitas Penggunaan Media Augmented Reality untuk Meningkatkan Hasil Belajar Siswa pada Mata Pelajaran Ilmu Pengetahuan Alam Kelas VIII MTsN 1 Solok Selatan - Devitri, Madella; Anugrah, Septriyan; Eldarni, Eldarni; Kurniai, Reni (Indo-MathEdu Intellectuals Journal, 2024)
Technological advances that can be used to increase knowledge are the development of information technology in the field of education. This study aims to determine the effectiveness of using Augmented Reality media to improve student learning outcomes in Natural Sciences teaching mates. Quantitative methods are used in the research. This study used a Quasi Experiment design, members of the experimental group as well as controls were not randomly selected. This study uses a nonequivalent control group design. This design is almost the same as the pretest posttest control group design. In this study, the sampling technique uses a purposive sampling technique. Based on the output of "Test Statistics", it is known that Asymp.Sig(2-tailed) has a value of 0.001. The basis for decision-making in the Wilcoxon test is if the Asymp.Sig value is < 0.05, then the hypothesis is accepted, if the Asymp.Sig value is 0.05, the hypothesis is rejected. The results of the analysis showed that there was an influence of the use of Augemented Reality media on student learning outcomes and that the media was effectively used in learning. The learning outcomes of students in grade VIII of Natural Sciences subject applied in grade VIII 4 as an experimental class obtained a higher average score of 86.37 while the average score obtained in grade VIII 3 as a control class was lower with an average of 82.89